Analisis Audit Energi Dalam Pencapaian Efesiensi Konsumsi Energi Listrik Kantor Bupati Kabupaten Sorong - Rahmad Hidayat Dongka; Reijeng Tabara (Electro Luceat, 2021)
High energy demand requires government office management to be efficient in its use. The Sorong Regency government office has several separate buildings. The main sources of electricity consumption come from PLN and the Power Diesel Engine Generator (DEG). With the condition of the building that is more than 10 years old, it is suspected that there will be a decrease in the efficiency of electrical equipment, an increase in energy consumption. If left unchecked, it will affect the safety and comfort of the building, energy efficiency, productivity, and performance of the employees who work, as well as the people who come to the building. This study aims to analyze the intensity of energy consumption (IKE) in the Sorong Regent's office building in order to get a value according to the standards that have been set. By analyzing the lighting load, and cooling load. The method used in this study is a quantitative descriptive analysis of the calculation of energy consumption intensity (IKE), lighting load and AC usage load. From the results of the study, it can be seen that the energy consumption index (IKE) in May was 8.1 so that it was included in the efficient category, then in June of 7.0 it was in the very efficient category, then in July it was in the very efficient category of 6.6, in August there was an increase of 9.1 so that it was included in the efficient category, in September it was 6.1 with very efficient criteria and in October it was in the efficient category which was about 8.4. Based on the average IKE of the Sorong Regency Regent's Office, it is in the range of 4-7 so that the Sorong Regency Regent's office building is included in the very efficient IKE category.